Extraordinary acts and ordinary pleasures: Rhetorics of inequality in young people's talk about celebrity. (July 2015) - Harvey, Laura; Allen, Kim; Mendick, Heather
In this article, we start from the problem of inequality raised by the existence of a class of celebrities with high levels of wealth and status. We analyse how young people make sense of these inequalities in their talk about celebrity. Specifically, we revisit Michael Billig's Talking of the Royal Family, and his focus on rhetorical strategies that legitimate inequalities of money and power. As he argued, in comparing their lives with those of the rich and famous, young people are making sense of the massive disparity between the two, often replacing envy or anger with pleasure in being 'ordinary'. We extend Billig's work by looking at a larger class of public figures than royalty, including those with a more permeable border between 'them' and 'us'. In so doing, we expand his categories and attend to the relationship between the gender of celebrities and contemporary rhetorics of inequality.